Resistance to Both Chemotherapy and EGFR-TKI in Small Cell Lung Cancer With EGFR 19-Del Mutation: A Case Report - Wang, Lingfei; Dong, Fangyuan; Su, Jie; Du, Guanjun; Shao, Yang; Liu, Ying; He, Xuequn; Bao, Liubin; Wang, Wei; Guo, Xin; Wang, Xi (Frontiers in Oncology, 2020)
Epidermal growth factor receptor (EGFR) mutations are common in non-small cell lung cancers, but rare in small cell lung cancers (SCLCs). In previous reports, some SCLC patients with EGFR mutations could benefit from EGFR tyrosine kinase inhibitors (TKIs). In this study, we reported a case in which a SCLC patient with EGFR exon 19 deletion (19-Del) mutation did not benefit from EGFR-TKIs. Interestingly, the standard treatment strategies for SCLC also failed to control tumor progression. Moreover, we screened 43 SCLC patients in China and found that the frequency of EGFR mutations in Chinese SCLC patients was about 4.65% by next generation sequencing (NGS). Collectively, this case illustrated a rare subtype of SCLCs which harbored EGFR mutations and was intrinsically resistant to standard treatments and EGFR-TKIs. We also tried to explore the mechanisms underlying drug resistance. The literature concerning SCLCs with EGFR mutations is reviewed.